Legal Analysis of The NFT (Non-Fungible Token) Based Digital Vaccine Certificate System in Digital Free Trade: Security, Privacy, and International Recognition Aspects - Sarmento Soares, Vasio; Wibowo, Sundaru Guntur; Anwar, Syahrul (Indonesian Cyber Law Review, 2025)
This study analyzes the legal framework of Non-Fungible Token (NFT)-based digital vaccine certificates in the context of digital free trade, focusing on security, privacy, and international recognition. Using normative and comparative legal research methods with a multidisciplinary approach, the study integrates perspectives from law, digital technology, and international policy. The study examines three main aspects: first, security, evaluating how NFTs ensure authenticity, data integrity, and protection against manipulation through encryption, blockchain, and smart contracts; second, privacy, analyzing how personal data and the privacy rights of certificate holders are protected under national and international regulations, emphasizing data minimization, user consent, and secure access; and third, international recognition, assessing the extent to which NFT-based certificates can be recognized globally, highlighting regulatory harmonization and legal barriers. The findings indicate that NFT-based vaccine certificates provide strong technical security and privacy protection, but legal recognition across jurisdictions remains inconsistent. The study concludes that while NFTs have significant potential to facilitate secure and verifiable digital health credentials in global trade, harmonization of national and international regulations and the implementation of legal standards are crucial to ensure their effectiveness and legal validity worldwide.